A Novel Method for non-contact measuring diameter parameters of wheelset based on wavelet analysis - Zhang, Zhifeng; Lu, Chao; Zhang, Fangzhen; Ren, Yufen; Yang, Kun; Su, Zhan (Optik (Stuttgart), 2012)
A railway wheelset is subject to normal wear due to large part to friction contact between the wheelset and the rail. It is very important to measure the diameter parameter of wheelset for the safety of trains. The optoelectronic method is introduced and can dynamically measure the diameter parameter. Fast Fourier transform and wavelet analysis methods are used to denoise the detected signals of wheelset diameters. The results show that the wavelet analysis provides a much better way of denoising of the signals compared with the fast Fourier transform method. Comparisons of the diameter parameter measurements with the manual apparatus and the optoelectronic system are presented. The measurement accuracy of diameter parameter was within 1.0mm. The root-mean-square error of the diameter is 0.51 and 0.15, respectively. The accuracy meets the measuring requirement of diameter parameters on line and shows that the system has better repeatability and reliability compared to the manual measurement.